Asesmen Kelayakan Material Praktek Konstruksi Baja di Teknik Sipil PNJ untuk Menghasilkan Produk Layak Jual - Mursid Mursid; Dyah Nurwidyaningrum; Yanuar Setiawan (Teknik Sipil, Politeknik Negeri Ketapangg, 2022)
Most of the Polytechnics in Indonesia currently function as workshops/labs/studios only as places for students to practice. As a result, student practice becomes a cost center for the cost of materials, maintenance, and development of practical machines, because the products produced by students do not meet industry standards to be worthy of sale. So, research was conducted to make a feasibility assessment of the practical steel construction materials at Civil Engineering PNJ to produce a product that is feasible to sell. The method used is testing the material properties of steel construction because of student practice and conducting a feasibility analysis of the steel construction material by comparing it to the quality standards in SNI. The results of material properties testing, and material feasibility assessment of steel construction can be concluded that the steel profile and connection plate used meet the quality standards with the BJ 55 and BJ 41 classifications, while the bolts used only meet the standard A370 bolt classification. So, it is recommended to use bolts with high quality bolt classification to meet the quality standards that exist in the industry.